2017
DOI: 10.1063/1.4986012
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structure of a current sheet in pulsed-power driven magnetic reconnection experiments

Abstract: We describe magnetic reconnection experiments using a new, pulsed-power driven experimental platform in which the inflows are super-sonic but sub-Alfvénic. The intrinsically magnetised plasma flows are long lasting, producing a well-defined reconnection layer that persists over many hydrodynamic time scales. The layer is diagnosed using a suite of high resolution laser based diagnostics which provide measurements of the electron density, reconnecting magnetic field, inflow and outflow velocities and the electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 41 publications
(72 reference statements)
4
49
0
Order By: Relevance
“…In carbon experiments however, the larger electron temperature of 60 eV results in a Lundquist number of S~100, which is sufficiently large that it is expected to place the layer in the plasmoid unstable, semi-collisional reconnection regime[41,42]. This is consistent with observations of the layer structure, which show the formation of plasmoids in both self-emission images [figure 3(b)] and laser interferometry[25,31,33]. Measurements with B-dot probes placed in the exhaust of the layer have indicated these indeed possess a magnetic O-point structure[25,31].…”
supporting
confidence: 83%
See 2 more Smart Citations
“…In carbon experiments however, the larger electron temperature of 60 eV results in a Lundquist number of S~100, which is sufficiently large that it is expected to place the layer in the plasmoid unstable, semi-collisional reconnection regime[41,42]. This is consistent with observations of the layer structure, which show the formation of plasmoids in both self-emission images [figure 3(b)] and laser interferometry[25,31,33]. Measurements with B-dot probes placed in the exhaust of the layer have indicated these indeed possess a magnetic O-point structure[25,31].…”
supporting
confidence: 83%
“…As the interaction of the magnetized flows occurs over a relatively long timescale, with a continuous inflow of the magnetized plasma for many times the hydrodynamic timescale of the system (T ≫ L V flow ⁄ ), the power balance can be monitored as the reconnection process develops and the system evolves. The results have shown that there is a transfer of the kinetic and magnetic energy of the inflowing plasma to the kinetic and thermal energy inside the layer [25,[30][31][32].…”
Section: Magnetic Reconnection In Counter-streaming Magnetized Plasmamentioning
confidence: 98%
See 1 more Smart Citation
“…Experiments with carbon wires produced super-sonic (M S = 1.7) but sub-Alfvénic (M A = 0.7) flows, which were accelerated to V = 50 km/s and advected a field of B = 3 T. 24,25 The flows propagated radially outwards from each wire, without shock formation between adjacent flows (Fig. 5a), which suggests the flows have a fast magneto-sonic Mach number…”
Section: B Results From Experiments With Carbon Wiresmentioning
confidence: 99%
“…For the parameters measured, plasmoids are expected to form in carbon, but not in aluminium, consistent with our observations. 15,25 There are clear differences between experiments with aluminium and carbon wires. The inflows in aluminium are more strongly driven and denser than those in carbon, and with more pronounced density modulations.…”
Section: B Differencesmentioning
confidence: 99%